ANALISIS WACANA PEMBIBITAN BAHASA INDONESIA DARI BARUS - Dewi Kartika Marioto; Suyadi Suyadi; Arianto Arianto (Balai Bahasa Sumatera Utara, 2022)
This study aims to describe and examine the process of breeding of Indonesian language from Barus, to describe the history of Barus, the figures who played a role in the breeding of Indonesian language from Barus, the reason Barus is called a megapolitan city, which made Barus famous from ancient times until now. This research was conducted by using discourse analysis using theory based on the views of Teun A. Van Dijk. This study uses a qualitative method with a descriptive approach to make a systematic, factual and accurate description of the data and the relationship between the events studied, in this study the data was collected by interviewing several sources. The results of this study are the character of Sheikh Hamzah Fansuri who is a Sufi as well as a writer who is believed by researchers that he comes from Barus, it can be proven by his work. He is a pioneer and contributes a lot to the vocabulary in terms of Indonesian language breeding, whose roots come from Malay and many absorptions from various other languages.